The Lost World's pristinity at risk. Issue Volume 22:Issue10(2016) (15th August 2016) - Rull, Valentí; Vegas‐Vilarrúbia, Teresa; Safont, Elisabet
Abstract: The Guayana Highlands (GH) are virtually pristine environments and constitute a unique natural laboratory to study the biogeographical and evolutionary origin of the Neotropical biota. In addition, the GH provide most of the water of the Guayana region, which feeds the more important tributaries of the Orinoco and the Amazon basins. However, the biota and the ecosystems of the GH are in danger of being profoundly altered by current human activities. Recent studies have identified the presence of aggressive invader plant species (e.g. Poa annua and Polypogon elongatus ) and infectious faecal bacteria ( Helicobacter pilori ), both carried by tourists, which could deeply affect biodiversity and ecological performance of terrestrial and aquatic GH ecosystems. If these hazards are not controlled as soon as possible, the potential consequences could disturb not only the GH ecosystems but also those of the rest of the Guayana region. We still have time to find solutions and implement specific regulations before the mentioned threats become uncontrollable. The GH are within a national park and other conservation figures but a management plan is lacking; therefore, current conservation rules are insufficient to deal with the newly detected menaces. We propose an international initiative, including all countries of the Guayana Shield, to take immediate actions. Otherwise, we are in danger of losing one of the few pristine biomes that remain in the world.